Evaluation of Prevalence and Severity of Anemia among Non-pregnant women of Reproductive Age in Garmian Province, Iraqi Kurdistan Region - Abdulraheem, Adnan Lateef; Rashid, Mustafa Younus; Faraj, Rahman Karim; Darwish, Rahma Qasim; Hama Amin, Gulzar Star; Muhialdin, Ali Jalak; Weli, Shwan Sardar (Iraqi Journal of Science, 2023)
Anemia is a major significant public health issue that affects both pregnant and non-pregnant women throughout the world. This study aimed to determine the prevalence and severity of anemia, as well as its classification, based on MCV values in non-pregnant women residing in the Garmian province in the east of Iraq. Blood samples were collected from non-pregnant women between the ages of 16 and 49 years. Anemia is classified as mild, moderate and severe, and as microcytic, normocytic and macrocytic depending on the level of Hb or mean corpuscular volume (MCV) respectively. In this study sociodemographic and hematological characteristics were also evaluated. The results showed that 56% of the study samples were anemic, and of the total anemic patients, 54 (35%), 86 (55%) and 16 (10%) had mild, moderate, and severe anemia respectively. Also, of the total anemic patients, 102 (65%) had microcytic type of anemia, 51 (33%) had normocytic anemia and only 3 (2%) had macrocytic anemia. The majority of anemic women (77.6%) had normal RBC counts but low Hct, MCH and MCHC values of 76.3%, 79.5% and 81.4%, respectively. The results showed also that there was no significant difference between the severity of anemia and age groups, occupation, blood pressure, bleeding, and haemorrhoids. However, diabetics showed a significant difference in anemia severity with <0.0004 P-value. The results showed that anemia had become a major public health issue in the study area.